Pengaruh Pertumbuhan Perusahaan, Kepemilikan Manajerial dan Kepemilikan Institusional Terhadap Nilai Perusahaan - Jullia, Mega; Finatariani, Endah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to examine and analyze the influence of managerial ownership and institutional ownership on firm value in non-cyclical consumer companies. This research uses quantitative methods and the data used is secondary data. The population in this study is non-cyclical consumer companies listed on the +Indonesia Stock Exchange for the 2018-2022 period. The method for determining the sample uses purposive sampling. A total of 113 companies were obtained over a 5 year period so that the total obtained was 28 sample data. The method used is multiple linear regression, descriptive statistical test, panel data regression model analysis, the selected model selection test is the Fixed Effect Model, classical assumption test, multiple linear test and hypothesis testing with the help of Eviews version 12 data processing. simultaneously shows that Company Growth, Managerial Ownership and Institutional Ownership which are proxied together have an effect on Company Value. The results of partial hypothesis testing show that company growth and institutional ownership have an effect on company value, while managerial ownership has no effect on company value.